Application of multi architecture modelling method in intelligent electric-vehicle design - Ma, Junda; Wang, Guoxin; Lu, Jinzhi; Zheng, Xiaochen; Yan, Yan (International journal of production research, 2025)
With the improvement of automobile intelligence, the research and development of the system is becoming increasingly complex and the development of the overall life cycle of the automobile system is facing increasing challenges. In this study, we propose a model-based systems engineering (MBSE) method through the development of multiarchitecture modelling language in order to support complex product development process modelling starting from the mission. Meanwhile, index verification and hybrid automaton simulations are employed to realise the static cost analysis of an architecture scheme and the rationality analysis of behaviour properties during the development process. Finally, a case of intelligent electric vehicle in a dual-vehicle system is established. In addition, the development process of mission-operation-feature/function-logic-physical (MOFLP) architecture is modelled and verified using multiarchitecture modelling language. Our results demonstrate that the multiarchitecture modelling language can support the multistage architecture description of the life cycle of complex products and perform static and dynamic analysis during the architecture description process.